Teacher Professional Allowance Implementation and Its Implications for Teacher Performance in Public Education Institutions - Purwadi Purwadi; Musmuliadi Musmuliadi; Sabran Sabran (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines the implementation of teacher professional allowance policy and its implications for teacher performance in public education institutions. As teachers play a central role in educational quality, professional allowance schemes are expected to function not only as financial support but also as policy instruments that strengthen motivation, discipline, and professional responsibility. This study employed a qualitative research approach using in-depth interviews with teachers, school leaders, and education administrators, supported by field observations to capture the actual conditions of policy implementation. The findings indicate that professional allowance is widely perceived as a form of recognition that enhances work motivation, responsibility, and discipline. However, the allowance does not automatically generate substantial improvement in instructional quality, particularly in institutional settings where academic supervision and performance monitoring remain limited. The policy contributes positively to administrative compliance and work discipline, yet its effect on pedagogical innovation and creative instructional practice is less evident. The effectiveness of the allowance system is influenced by intrinsic motivation, leadership support, and the clarity and transparency of administrative procedures. The study highlights the importance of a more integrated management approach that combines professional allowance policy with continuous professional development, institutional support, and stronger evaluation mechanisms to maximize its contribution to teacher performance and educational quality.